2002
DOI: 10.1063/1.1512993
|View full text |Cite
|
Sign up to set email alerts
|

Nickel antidot arrays on anodic alumina substrates

Abstract: Large area nickel antidot arrays with density up to 10 10 /cm 2 have been fabricated by depositing nickel onto anodic aluminum oxide membranes that contain lattices of nanopores. Electron microscopy images show a high degree of order of the antidot arrays. Various sizes and shapes of the antidots were observed with increasing thickness of the deposited nickel. New features appear in the antidot arrays in both magnetization and transport measurements when the external magnetic field is parallel to the current d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
87
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 32 publications
4
87
0
Order By: Relevance
“…Among the magnetic nanostructures that can be obtained by using self-organized processes there are the so-called magnetic antidots (i. e. holes arrangement embedded into a continuous magnetic film). In effect, the use of self-organized ordered nanoporous alumina membranes as templates has allowed the fabrication of magnetic antidots films with high hexagonal order and controlled pores distribution [9]. Magnetic antidots are a topic of intense current research since they are promising candidates for high-density information storage as well as a very exciting topic in fundamental physics [10,11,12,13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Among the magnetic nanostructures that can be obtained by using self-organized processes there are the so-called magnetic antidots (i. e. holes arrangement embedded into a continuous magnetic film). In effect, the use of self-organized ordered nanoporous alumina membranes as templates has allowed the fabrication of magnetic antidots films with high hexagonal order and controlled pores distribution [9]. Magnetic antidots are a topic of intense current research since they are promising candidates for high-density information storage as well as a very exciting topic in fundamental physics [10,11,12,13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…2 One common feature in many of these magnetic nanostructures, such as magnetic nanorings, [3][4][5][6] thin films patterned with arrays of antidots, [7][8][9][10][11][12] or magnetic disks with controlled defects, 13 is the existence of nonmagnetic holes within the magnetic material. Most of the attention has been devoted to the analysis of the different magnetic configurations corresponding to each different kind of structure, such as the transitions between in-plane axial and vortex states in nanorings, 14 or the different kinds of periodic closure domain structures in magnetic films with antidots.…”
Section: Introductionmentioning
confidence: 99%
“…It can be further tested by etching alumina membranes containing highly ordered pore arrays with uniform pore sizes. Previous reports 18,26,27 have shown that it is possible to obtain such alumina membranes by strictly controlling the anodization conditions. In fact, alumina nanowires with diameters on the order of only 5 nm, as expected from case B of Figure 3a, have been observed during the etching of alumina membranes with highly ordered arrays of uniform pores.…”
mentioning
confidence: 99%